2014
DOI: 10.1088/0964-1726/23/4/045030
|View full text |Cite
|
Sign up to set email alerts
|

An active viscoelastic metamaterial for isolation applications

Abstract: Abstract. Metamaterials are of interest due to their ability to produce novel acoustic behaviour beyond that seen in naturally occurring media. Of particular interest is the appearance of band gaps which lead to very high levels of attenuation within narrow frequency ranges. Resonant elements within metamaterials allow band gaps to form within the long wavelength limit at low frequencies where traditional passive isolation solutions suffer poor performance. Hence metamaterials may provide a path to high perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Their work was, however, a small-scale study in the laboratory. Their pioneering work brought forth a new field of research in various disciplines such as transformation optics [Jiang et al, 2009;Kinsler and McCall, 2015;Lu et al, 2009] energy harvesting , noise barriers [Garcia-Chocano et al, 2012;Garcia-Chocano and Sanchez-Dehesa, 2013;Ho et al, 2003;Lagarrigue et al, 2013;Sanchez-Dehesa et al, 2011] and vibration/shock mitigation [Akl and Baz, 2012;Baravelli and Ruzzene, 2013;Huang and Sun, 2010;Kim et al, 2015;Pai et al, 2014;Peng and Pai, 2014;Reynolds and Daley, 2014;Sharma and Sun, 2015;Tan et al, 2012]. The consideration of using AMs specifically for cavity noise control has been reported recently in two separate works.…”
Section: The Emergence Of Acoustic Metamaterialsmentioning
confidence: 99%
“…Their work was, however, a small-scale study in the laboratory. Their pioneering work brought forth a new field of research in various disciplines such as transformation optics [Jiang et al, 2009;Kinsler and McCall, 2015;Lu et al, 2009] energy harvesting , noise barriers [Garcia-Chocano et al, 2012;Garcia-Chocano and Sanchez-Dehesa, 2013;Ho et al, 2003;Lagarrigue et al, 2013;Sanchez-Dehesa et al, 2011] and vibration/shock mitigation [Akl and Baz, 2012;Baravelli and Ruzzene, 2013;Huang and Sun, 2010;Kim et al, 2015;Pai et al, 2014;Peng and Pai, 2014;Reynolds and Daley, 2014;Sharma and Sun, 2015;Tan et al, 2012]. The consideration of using AMs specifically for cavity noise control has been reported recently in two separate works.…”
Section: The Emergence Of Acoustic Metamaterialsmentioning
confidence: 99%
“…[7][8][9][10][11] Most of these works mainly focused on the transmission properties of the resonant material and highlighted the large transmission dip at the HR resonance frequency. [7][8][9] Boutin and B ecot, 11 Lagarrigue et al, 12 and Groby et al 13 recently investigated the sound absorption efficiency of rigid backed acoustic foams with resonant split hollow cylinder or HR inclusions and showed that it is greatly improved for frequencies with a wavelength much larger than the material thickness.…”
Section: Haisam Osmanmentioning
confidence: 99%
“…2a. As shown in Reynolds and Daley (2014) this can be explained using the Bloch dispersion relationship of a the periodic metamaterial given by Eq. 4, where kd is plotted in Fig.…”
Section: The Active Viscoelastic Metamaterialsmentioning
confidence: 99%
“…Although an experimental metamaterial was produced by Reynolds and Daley (2014) that demonstrated the potential of the active control architecture, the paper contained only preliminary proof of concept results. Moreover the viscoelastic metamaterial was produced using additive layer manufacturing techniques that limited the passive performance of the isolation device.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation